Rest in Mesopotamian and Israelite literature - Kim, Daniel E. (Perspectives on Hebrew scriptures and its contexts, 2019)
"Rest in Mesopotamian and Israelite Literature studies the concept of rest in the Hebrew Bible and ancient Near Eastern literature. Through close examination of Mesopotamian texts and selections from the Deuteronomistic History and Chronicles, Kim delineates a concept of rest for each body of literature, and employs a comparative approach to illuminate the rest motif in the Hebrew Bible in light of Mesopotamian literature"--